PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN SELAMA COVID-19 DI UNIVERSITAS BOSOWA : STUDENT’S PERCEPTION AT LEARNING PROCESS DURING COVID-19 IN BOSOWA UNIVERSITY - Rasyidah Zainuddin; Muhammad Masdar; Andi Burchanuddin (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MEGAREZKY, 2021)
This study aims to describe (1) the implementation of sociology learning at the Sociology Study Program at Bosowa University, (2) students' perceptions of sociology learning at the Sociology Study Program at Bosowa University Makassar. This study uses a quantitative descriptive method with a survey approach to all 100 students of the sociology study program. The number of this population as well as the research sample. Data collection techniques used research instruments with a five-scale Likert scale, and literature study. Data analysis technique used frequency tabulation with percentage technique. The results of the study found: (1) The implementation of learning during the COVID-19 pandemic was categorized as 'Good' with a score of 245, sometimes 50, Bad 49. (2) Respondents' perceptions of the implementation of learning during the COVID-19 pandemic were categorized as 'Good' (Score 322). , Average (Score 44), Bad (Score 9). The conclusion of the study is that students' perceptions of learning during the Covid-19 Pandemic at the University of Bosowa are categorized as 'Good'. The recommendation of this research is the need for teachers to innovate learning in the post-pandemic era in order to keep up with the times. Penelitian ini bertujuan untuk menggambarkan (1) implementasi pembelajaran sosiologi di Program studi sosiologi Universitas Bosowa, (2) persepsi mahasiswa terhadap pembelajaran sosiologi di program studi sosiologi Universitas Bosowa Makassar. Penelitian ini menggunakan metode deskriptif kuantitatif dengan pendekatan suvei terhadap semua jumlah mahasiswa program studi sosiologi sebanyak 100 orang. Jumlah populasi ini sekaligus juga sebagai sampel penelitian. Teknik pengumpulan data mempergunakan instrumen penelitian dengan Skala Likert lima skala, dan studi kepustakaan. Teknik analisis data menggunakan tabulasi frekuensi dengan teknik persentase. Hasil penelitian menemukan : (1) Implementasi pembelajaran selama pandemi covid-19 terkategori ‘Baik’ dengan nilai 245, kadang-kadang 50, Buruk 49. (2) Persepsi responden terhadap implementasi pembelajaran selama pandemi covid-19 terkategori ‘Baik’ (Nilai 322), Biasa (Nilai 44), Buruk (Nilai 9). Kesimpulan penelitian adalah persepsi mahasiswa terhadap pembelajaran selama Pandemi Covid-19 di Universitas Bosowa terkategori ‘Baik’. Rekomendasi penelitian ini adalah perlunya para guru melakukan inovasi pembelajaran di era post-pandemi agar dapat mengikuti perkembangan zaman.